Modeling morphodynamic processes in a meandering river with unmanned aerial vehicle-based measurements - Akay, Semih Sami; Ozcan, Orkan; Sen, Omer Lutfi (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2019)
Change detection analysis for monitoring and modeling riverine systems requires detailed spatial and temporal surveying of river morphology dynamics. Accurate digital surface models are an essential part of the studies of morphodynamic modeling of rivers and river channel evolution. An accurate high-resolution surface model of the river channel and floodplain enables a more comprehensive view of the riverbed evolution and allows monitoring of morphological changes of the entire river channel more precisely compared with traditional methods. In current practice, unmanned aerial systems (UAS) are widely used for various applications in photogrammetry, especially for three-dimensional surface modeling and large-scale mapping of riverine environments. UASs offer many advantages in terms of cost and image resolution and approaches for mapping across varying spatial extents when compared with terrestrial photogrammetry and satellite remote sensing systems. UAS-based aerial mapping was implemented in order to produce very high resolution surface models of a flood-sensitive region based on structure from motion technique. Ultimately, multitemporal topographic data were produced, and morphodynamic processes in the lower course of the Buyuk Menderes River in Turkey were modeled by digital shoreline analysis system and digital elevation model of difference methods. These methods were employed to examine the changes in the shoreline and to analyze the size of geomorphological changes and spatial patterns. The results showed that the change in the shoreline of the meanders varied from 3 to 27 m, and the water levels varied between similar to 0.3 and 3 m. Although there was both sediment erosion and deposition along the shoreline, the predominant process was identified as deposition in the shoreline. A significant correlation was found between the deposited sediments and the sinuosity index values (r = 0.88) according to the changes in water level over the months. In addition, major changes on the deposition rate were found to occur mostly after the summer season. This research showed that UASs could provide a suitable measurement model for determining areal and volumetric eroded/deposited sediment quantities along the meandering fields. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: Buyuk; Menderes River; structure from motion; erosion; river morphology; STRUCTURE-FROM-MOTION; BUYUK MENDERES; TOPOGRAPHIC SURVEYS; WESTERN ANATOLIA; UAV IMAGERY; MORPHOLOGY; RECONSTRUCTION; PHOTOGRAMMETRY; DYNAMICS; Environmental Sciences & Ecology; Remote Sensing; Imaging Science & Photographic Technology